Attention-Deficit Hyperactivity Disorder Status and Baseline Neurocognitive Performance in High School Athletes. Issue 4 (1st October 2016) - Salinas, Christine M.; Dean, Preston; LoGalbo, Anthony; Dougherty, Michael; Field, Melvin; Webbe, Frank M.
Abstract : Approximately 136, 000 concussions occur annually in American high school sports. Neuropsychological data indicate that children with preexisting cognitive difficulties, such as attention-deficit hyperactivity disorder (ADHD), may have protracted recovery from concussion. ADHD, with an estimated prevalence of 11% in youth, may increase an athlete's vulnerability to sustaining sports-related traumatic brain injury (TBI). The preponderance of evidence focusing on TBI and ADHD has derived from motor vehicle accidents rather than sports-related incidents. Thus, it is paramount to explore how ADHD may relate to injury in the sports concussion context, as well as to assess how ADHD may affect baseline neurocognitive testing. Adolescent athletes with ADHD ( n  = 256) demonstrated significantly reduced Verbal Memory, Visual Motor, and Impulse Control index scores compared with their peers without ADHD ( n  = 256). Athletes with ADHD were nearly twice as likely to have sustained a prior concussion (ADHD, 14.1%; non-ADHD, 7.8%). Knowledge regarding the unique neurocognitive profile of athletes with ADHD may enhance clinical management decisions.